Digital governance pathways: Multidimensional challenges in the absence of a scientific foundation are not a deterrent to successful implementation - Subhasis Bera; Dil Bahadur Rahut; Yixin Yao (Asian Development Bank Institute (ADBI), 2023)
It is challenging for policymakers to administer diverse technological, social, and cultural setups by expeditiously addressing local problems in a country. Successful digital governance encompasses norms, institutions, and standards to regulate the development and use of digital technologies to ensure equality by addressing multidimensional issues. By considering the evolution of digital governance, this study explains how the complexity of its successful implementation arises from issues at the digitalization level, the geopolitics of global cyberspace governance, stakeholder engagement, knowledge base augmentation, and an entanglement of the digital and physical worlds. This study proposes stakeholder participation through citizen-generated data and enabling digital logistic platforms to support the entanglement of the digital and physical worlds to unlock the potential of digital governance.
Keywords: H11; H70; O1; O32; P2; 330; digital governance; digitalization; networking; geopolitics; knowledge economy; citizen-generated data